Capital income taxation incentives during economic downturns: Re-thinking theory and evidence - Ernesto Longobardi; Vito Polito (Cardiff University, Cardiff Business School, 2011)
This paper studies the effectiveness of corporate tax incentives in reducing the effective tax rate (ETR) on income from capital to stimulate business investment during economic downturns. We focus on tax rate incentives (TRIs), such as corporate tax rate cuts, and tax base incentives (TBIs), such as increased capital allowances. The standard economic theory states that TRIs reduce the ETR by decreasing tax payments on corporate profits. TBIs instead reduce the ETR as they defer firms tax payments, in turn increasing the present value of dividend distribution. However, this theory does not consider that, in reality, firms face accounting constraints preventing any distribution of cash flows arising from TBIs. For this reason, the standard economic analysis overstates the benefit of any TBI relative to that of TRIs. The paper incorporates accounting constraints on dividend policy into the model for the computation of the ETR and employs the new model to recalculate ETRs in the US and in the UK during 1980-2010. The empirical results confirm that the benefit of TBIs is significantly overstated by the standard theory, and tax rate cuts are more effective in reducing the ETR. We show that this result holds regardless of the form of investment finance (retained earning, new equity and debt), the type capital asset (building and plant and machinery), the level of capital income taxation (corporate and shareholders), and the value of accounting depreciation relative to economic depreciation.
Keywords: H3; 330; capital income taxation; dividend policy; effective marginal tax rates; financial constraints; Konjunktur; Verschuldungsrestriktion; Unternehmensbesteuerung; Dividende; Optimale Besteuerung; Großbritannien; USA